A Study on the O2 Plasma Etching Method of Spray-Formed SWCNT Films and Their Utilization as Electrodes for Electrochemical Sensors - Jinkyeong Kim; Ji-Hoon Han; Joon Hyub Kim (Sensors, 2023)
In this study, we analyzed the morphological changes and molecular structure changes on the surface of single-walled carbon nanotube (SWCNT) films during oxygen plasma (O2) etching of SWCNT surfaces formed by the spray method and analyzed their potential use as electrochemical electrodes. For this purpose, a SWCNT film was formed on the surface of a glass substrate using a self-made spray device using SWCNT powder prepared with DCB as a solvent, and SEM, AFM, and XPS analyses were performed as the SWCNT film was O2 plasma etched. SEM images and AFM measurements showed that the SWCNT film started etching after about 30 s under 50 W of O2 plasma irradiation and was completely etched after about 300 s. XPS analysis showed that as the O2 plasma etching of the SWCNT film progressed, the sp2 bonds representing the basic components of graphite decreased, the sp3 bonds representing defects increased, and the C–O, C=O, and COO peaks increased simultaneously. This result indicates that the SWCNT film was etched by the O2 plasma along with the oxygen species. In addition, electrochemical methods were used to verify the damage potential of the remaining SWCNTs after O2 plasma etching, including cyclic voltammetry, Randles plots, and EIS measurements. This resulted in a reversible response based on perfect diffusion control in the cyclic voltammetry, and an ideal linear curve in the Randles plot of the peak current versus square root scan rate curve. EIS measurements also confirmed that the charge transfer resistance of the remaining SWCNTs after O2 plasma etching is almost the same as before etching. These results indicate that the remaining SWCNTs after O2 plasma etching do not lose their unique electrochemical properties and can be utilized as electrodes for biosensors and electrochemical sensors. Our experimental results also indicate that the ionic conductivity enhancement by O2 plasma can be achieved additionally.